Toolkits for dissemination and implementation research: Preliminary development. Issue 4 (27th November 2018) - Baumann, Ana A.; Morshed, Alexandra B.; Tabak, Rachel G.; Proctor, Enola K.
Abstract : The Dissemination and Implementation Research Core, a research methods core from the Clinical and Translation Science Award at Washington University in St. Louis Institute of Clinical and Translational Sciences, developed toolkits about dissemination and implementation (D&I) concepts (e.g., D&I outcomes, strategies). This paper reports on the development of the toolkits. These toolkits respond to 3 identified needs for capacity building in D&I research: resources for investigators new to the D&I field, consolidation of tools, and limitations in local contexts.